Analysis Of Factors Influencing The Community In The Conversion Of Paddy Fields In The West Nusa Tenggara Province - Haero Ummah, Gina; Baiq Saripta Wijimulawiani; Muhammad Dzul Fadlli (Cita konsultindo, 2025)
Abstract This study analyzes the factors influencing people to convert paddy fields in West Nusa Tenggara Province. The factors examined include gender, age, certified land area, credit, and rice production. This research used an associative quantitative method using secondary data from the Central Statistics Agency (BPS) in 2013 and the Agriculture and Plantation Office of West Nusa Tenggara Province in 2020-2023. The data were analyzed using logistic regression to test the relationship between socioeconomic variables and land conversion decisions. The results showed that certified land area significantly affected land conversion decisions. Gender, age, credit, and rice production negatively affect land conversion decisions, indicating a tendency for good credit management and increased rice production to reduce the tendency of conversion of paddy and non-paddy land.